A contingent valuation study of Winnipeg municipal water using bounded rationality. (1st January 2002) - McComb, Greg
Contingent valuation (CV) is a survey technique used to value environmental goods not traded in markets, such as improvements to air or water quality. Despite its popularity, widespread acceptance of this methodology has been hampered by controversies stemming from numerous behavioural anomalies such as preference reversals, embedding and starting point bias. This study argues that these anomalies are better understood using bounded rationality to model behaviour, rather than traditional economic theories of rationality. To demonstrate this, a conceptual framework is developed which explains the various aspects of bounded rationality. This framework is then applied to a literature review and a CV experiment that values an improvement to municipal water quality in Winnipeg, Canada. The results indicate that the research design mitigated many possible anomalies and that bounded rationality provided a useful conceptual framework to understand anomalous results that did arise.